COVID‐19 and water demand: A review of literature and research evidence. (25th November 2021) - Cahill, Joseph; Hoolohan, Claire; Lawson, Rob; Browne, Alison L.
Abstract: COVID‐19 has had unprecedented impacts across the international community, with complex and far‐reaching consequences. Measures to prevent transmission have led to substantial changes to everyday life, with lockdowns, stay‐at‐home orders and guidance leading to an increase in people staying indoors. This movement of activity had profound impacts on daily practices, affecting the consumption of resources including water. Likewise, Water, Sanitation and Hygiene (WASH) practices and infrastructure are crucial tools for the management of disease. Therefore, this review seeks to assess the current literature on the impact of COVID‐19 on domestic water use. A web‐based rapid evidence review was undertaken to assess and synthesize the theories, methods and empirical evidence emerging across a multidisciplinary body of research to understand how COVID‐19 effects everyday water use. Key themes around increased water consumption and changing daily consumption patterns emerged. There was a distinct lack of social science concepts and methodologies in use to understand changing water demand, and the methodological focus was largely quantitative. Key insights and reflections were lacking as a result, for example, there was little research on how the water‐related practices, consumption, and demand patterns differed among households. This article makes the case for further qualitative and mixed‐method research using social theories, illustrating how social practice theories, as one example, contribute to understanding the dynamics of everyday life during the pandemic. This research would generate deeper understandings of the impacts of COVID‐19 on domestic water use as well as an evaluation of the implications these findings could have post‐pandemic. This article is categorized under: Engineering Water > Methods Engineering Water > Water, Health, and Sanitation Engineering Water > Planning Water Abstract :